How data journalism changing newsrooms in Kazakhstan (Herald of Journalism, 2022)
This study examines how data journalism Changing newsrooms in Kazakhstan. Internet plays a sig- nificant role as a modern communication tool in Kazakhstan. The analysis examines whether the process of changing and establishing newsrooms and media as an influence of the new informational technol- ogy. Key to this effort was establishing the Digital Journalism and Data Journalism as a revolution in communications technology is clearly changing the media style, and it has created a highly competitive environment for those who provide news and information to the public. At the time of independence an overwhelming majority of Kazakhstani media changed from traditional to online, which remains strong today. Interviews were conducted with key members of Kazakhstani media industry to learn the role of data journalism in establishing and changing the newsrooms. The author of this study are discussed in de- tail the utility and its implications of the role of data journalism in the modern newsrooms in Kazakhstan.Key words: Internet, Data Journalism, Digital Journalism, communication technology, Kazakhstan.